Pengaruh Metode Proyek terhadap Motivasi Belajar Siswa Kelas VI pada Pembelajaran Tematik di Madrasah Ibtidaiyah Al Abrar Cinnong Kec. Lappariaja Kab. Bone: Metode Proyek terhadap Motivasi Belajar Siswa - Nur Rahmatan Mursalin; Mustanil (IAI DDI POLEWALI MANDAR, 2022)
The purpose of this study was to determine how the effect of the project method on the learning motivation of grade VI students in thematic learning at Madrasah Ibtidaiyah Al Abrar Cinnong, Lappariaja District, Kab. Bone. This study uses an experimental type of research with the research design used is One Group Pre-test and Post-Test. The data collection techniques used observation, tests, questionnaires and documentation. The test was used to obtain data on the learning outcomes of the sixth grade students of Madrasah Ibtidaiyah Al Abrar Cinnong, questionnaires were used to determine student learning motivation, while observation and documentation were used to explore data on thematic learning by applying project methods and student activities during the thematic learning process. Then the data analysis was carried out using statistical analysis, namely thitung test analysis to determine the effect of the project method on students' learning motivation. The results showed that the tcount value was 3.19954 and the ttabel value obtained in the distribution table of the t-value with a significance level of 0.05 was 1.75305. Then it can be seen that tcount is greater than ttable, namely 3.19954>1.75305. This means that the hypothesis is accepted. Thus, there is an effect of the project method on the learning motivation of grade VI students in thematic learning at Madrasah Ibtidaiyah Al Abrar Cinnong, Lappariaja District, Kab. Bone. Keywords: Project Method, Learning Motivation, Thematic Learning